PENGARUH KECUKUPAN MODAL, RISIKO KREDIT, BIAYA OPERASIONAL PENDAPATAN OPERASIONAL PADA PROFITABILITAS BANK - Edy Saputra, I Made Hendra; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
This study aimed to determine the effect of capital adequacy, credit risk and operational costs operating income (ROA) on the profitability of banks listed on the Stock Exchange. The data used in this study were obtained from published financial statements of banking companies listed on the Stock Exchange from the year 2009-2013 with a sample of 26 banking. The data analysis technique used is multiple linear regression with applications SPSS.Berdasarkan analysis showed that partial capital adequacy positive effect on the profitability of banks listed on the Stock Exchange in 2009-2013, while the credit risk and operational costs of operating income (ROA) negative effect on Bank profitability listed on the Stock Exchange in 2009-2013.
Keywords: Capital Adequacy, Credit Risk, Operational Costs Operating Income, Bank Profitability